2021
DOI: 10.1021/acsomega.1c00302
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Gut Microbiota Using Acacia Gum Polysaccharide

Abstract: Acacia gum (AG) is a branched-polysaccharide gummy exudate that consists of arabinose and galactose. The traditional practice in African-Middle Eastern countries uses this gum as medicine. Traditional use of AG is to treat stomach disease, which can be a potential functional food. In this research, commercially available AG from Acacia senegal and Acacia seyal was investigated as the prebiotic. The experiment employed a pH-controlled in vitro colon model inoculated with human fecal microbiota to mimic the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 138 publications
0
14
0
Order By: Relevance
“…The OAs, including short-chain fatty acids (SCFAs), can substitute AGPs from broiler diets (Scicutella et al 2021 ). The SCFAs, majorly propionic acid, acetic acid, and butyric acid, are produced by the fermentation of the carbohydrates performed by beneficial intestinal bacteria (Rawi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The OAs, including short-chain fatty acids (SCFAs), can substitute AGPs from broiler diets (Scicutella et al 2021 ). The SCFAs, majorly propionic acid, acetic acid, and butyric acid, are produced by the fermentation of the carbohydrates performed by beneficial intestinal bacteria (Rawi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of an in vitro study by Rawi et al showed that acacia gum significantly increased the abundance of Bifidobacteria while it inhibited that of Clostridium histolyticum, the bacterium which gives rise to gut dysbiosis. Moreover, acacia gum promoted the production of butyrate, which may also contribute to ameliorating the gut microbiota [49]. RSs, both insoluble and soluble, can be fermented and utilized by colonic microorganisms.…”
Section: Effects Of Sdfs On the Gut Microbiotamentioning
confidence: 99%
“…[158]. A commercial prebiotic containing the polysaccharides from Acacia senegal and Acacia seyal, used in an in vitro study involving an artificial intestine settled by human fecal microflora, caused an increase in the number of Bifidobacteria and a decrease in the number of Clostridium histolyticum, as well as an increase in SCFA content [202]. Some prebiotics benefit gut health by selectively stimulating gut microorganisms, including Bifidobacteria [203].…”
Section: Communication Between Microorganisms and Epithelial Cells Re...mentioning
confidence: 99%